2009
DOI: 10.1186/ar2659
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with urate-lowering therapies for the treatment of gout

Abstract: Introduction Adherence to urate-lowering drugs (ULDs) has not been well evaluated among those with gout. Our aim was to assess the level and determinants of non-adherence with ULDs prescribed for gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 18 publications
12
112
1
3
Order By: Relevance
“…Importantly, this possibility suggests that our estimate of SU goal knowledge, although quite low, is likely higher than would be seen in a broader patient population. Our study also indicated high levels of medication adherence for both questionnaire responders and nonresponders relative to other recent studies (15,(37)(38)(39)(40)(41). The PDC values in our study are higher than in other studies, likely due to the high proportion of prevalent users in our cohort and the use of mailed prescriptions in the VA system.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, this possibility suggests that our estimate of SU goal knowledge, although quite low, is likely higher than would be seen in a broader patient population. Our study also indicated high levels of medication adherence for both questionnaire responders and nonresponders relative to other recent studies (15,(37)(38)(39)(40)(41). The PDC values in our study are higher than in other studies, likely due to the high proportion of prevalent users in our cohort and the use of mailed prescriptions in the VA system.…”
Section: Discussionsupporting
confidence: 58%
“…(14) Adherence rates to pharmacotherapy in gout are particularly poor, ranging from 18%-44%, and significantly lower than those in patients with other chronic diseases. (15,16) Reasons offered by patients who were nonadherent include the belief that they were cured, fear of side effects and pill burden; (14) this is especially relevant in the local context as most formulations of allopurinol are only available in 100-mg tablets.…”
Section: Patient Factorsmentioning
confidence: 99%
“…This hypothesis is consistent with: (1) the frequent association between several manifestations of nonadherence and smoking and alcohol habits: for instance, smoking and excessive alcohol consumption are independent predictors of low practice of self-monitoring of blood glucose in diabetic patients [39]; (2) the effect of young age on non-adherence in chronic diseases [7]; (3) the frequency of non-adherence in teenagers (an experimental study showed that adolescents and people in their twenties have more difficulties in finding similarities between them now and them in the future than older people [40]); (4) the fact that the level of maturity is associated with adherence to immunosuppressive drugs in adolescent and young adults following heart transplantation [41]; (5) data from fMRI studies, providing the evidence that the balance between frontal and limbic circuitries is relatively late maturing during the brain development from childhood to adult age [42,43]: it is tempting (even if hazardous) to see an explanation of a risk in teenagers, not only for addiction, but also for poor adherence; (6) the effect of social deprivation on non-adherence to medication [44]: a shorter temporal horizon was found to be associated to a lower income [38]; (7) the effect of education on adherence to medication and other health behaviours [45]: a stronger future orientation of women, who asked more frequently for BRCA1/2 screening and mammography, was seen in women who had higher levels of education [35]; and finally (8), this explanation may represent a common link leading to a clustering of preventive behaviours in some individuals, this concept of 'healthy adherer' explaining the puzzling observation that adherence to a placebo is associated with a decrease in mortality [46].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the lowest adherence was observed in patients with gout, a disease which can take the form of a painful crisis. More surprisingly, a recent study showed that use of non-steroidal anti-inflammatory drugs in the year prior to urate-lowering drug initiation (suggesting the occurrence of a crisis), was a significant predictor (OR 1.15, 95% CI 1.00-1.31) of poor adherence to subsequent gout therapy [8]. These observations contradict the common view that non-adherence is especially frequent in 'silent' diseases such as diabetes.…”
Section: Introductionmentioning
confidence: 87%